Pokryzysowa zmiana - Szymanowski, Rafał (Wydawnictwo Naukowe WNPiD UAM, Poznań, 2011)
Bankruptcy of Lehman Brothers, the 4th largest investment bank in the USA and the collapse of a financial sector initiated the biggest economic crisis since the Great Depression. Global recession sparked off an ongoing public debate. The main concern is whether it is an ordinary slubp or a serious systemic crisis. This article highlights two crucial changes appearing on the horizon of the post-crisis world: the death of a neo-liberal doctrine and „rising tide” of women.
The Post-Crisis Change
Keywords: deregulacja; kryzys; liberalizm; finanse